PEMANFAATAN BUAH PEDADA (Sonneratia caseolaris) DALAM PEMBUATAN SIRUP DAN TEH HERBAL DESA IBRU KECAMATAN MESTONG MUARO JAMBI - Maryani, Anis Tatik; Asra, Revis; Ichwan, Budiyati; Eliyanti, Eliyanti; Renate, Dharia; Huda, Nur (LPPM Universitas Islam 45 Bekasi, 2025)
The pedada fruit (Sonneratia caseolaris) comes from mangrove trees that grow in coastal areas. This fruit is rich in vitamins A, B1, B2, and C, which are essential for the body’s metabolism. However, its sour taste often makes many people reluctant to consume it directly. Typically, communities process this fruit into various foods. Unfortunately, a lack of knowledge about the nutritional content of pedada fruit leads to suboptimal utilization. Therefore, processing pedada fruit into herbal products is a valuable innovation. Environmentally friendly processing methods, such as making syrup and herbal tea, reduce dependence on harmful chemicals and support sustainable agricultural practices. Additionally, training and entrepreneurship development in villages encourage communities to be more environmentally conscious, recognizing the importance of preserving mangrove plants as supporters of biodiversity. Thus, this initiative not only improves economic welfare but also contributes to the preservation of the surrounding environment. Innovative processing of pedada fruit serves as a solution for utilizing natural resources and enhancing production in Ibru Village, Mestong District, Muaro Jambi. The nutrient-rich pedada fruit is often neglected and underutilized. This project involves a service team from the University of Jambi collaborating with small and medium enterprises (SMEs) to enhance community knowledge and skills in processing this fruit into herbal tea and syrup.